When Vocational Teachers Improve Their TPACK Competencies ThroughLesson Study - Wagiran (International Journal of Psychosocial Rehabilitation, 2020)
— Teachers at vocational schools may be more challenged than at public high schools since they aim to teach working skills that could be more complex than just knowledge. The paper aims to propose models of lesson study for vocational teachers. It is proposed that when vocational teachers utilizelesson study to improve pedagogic competencies, a strategy to implement it is required to minimize possible obstacles.Further, through a systemmatic review, the perspective of Technical Pedagogical and Content Knowledge (TPCK) is used to develop the model of the teacher professionalism.A lesson study strategy is choosen depending on the focus of the professionalism by identifying pedagogic and content competencies level of the involving teachers. Four types of teachers based on these dichotomies were developed, and therefore four models of lesson study could be derived. The models offer what specific competence to learn during the lesson study. Through the use of the lesson study model, vocational teachers in across different fields could decide the most relevant model of their professionalism, with regard to their competence in pedagogic, content, or technological knowledge. Eventually, the lesson study model becomes a strategic pathway to solve issues in vocational education.Improvement of the effectiveness lesson study practice when suitable model is applied can be achieved. This paper offers lesson study models that are developed based on teacher typology of competence, particularly for vocational teachers with wide-range of specialities